Study to evaluate the effectiveness of coagulation factor concentrate prophylaxis in children with severe hemophilia - Udayakumar, S; Pushpalatha, K; Vinayaka, K; Sushma, C; Swathi, P M (Indian Journal of Child Health, 2017)
Objective: To evaluate the effectiveness of prophylaxis with coagulation factor concentrates VIII/IX (FVII/IX) in children with severe hemophilia A/B, respectively. Materials and Methods: Retrospective observational study was done on children enrolled in our hemophilia clinic, who initially received “on demand” therapy and were on prophylaxis with factor VIII/IX concentrate at the time of the study. The study group consisted of 8 children. Annual hemarthrosis rate (AHR) over a period of 1-year during on demand therapy was compared with AHR during a period of 1-year on prophylaxis with FVIII/IX. Results: There was reduction in AHR by 87% in hemophilia A and 85% in hemophilia B during prophylaxis compared to on demand therapy. There was a significant reduction in hemarthrosis/patient/year from 2.5 to 0.3 on prophylaxis with factor concentrate compared to on demand therapy. There was also reduction in other bleeding manifestation like psoas muscle bleed, oral bleeds, epistaxis, and number of target joints involved. Conclusion: Prophylaxis with coagulation factor concentrate significantly reduces the AHR, and hence, decreases the disability associated with it compared to “on demand” therapy.